Geheime Figuren der Rosenkreuzer: esoterismo no imaginário do movimento Rosacruz do século XVIII - Amorim, José Carlos de Abreu (2016)
This work aims at a symbolic analysis of the Geheime Figuren der Rosenkreuzer work aus dem 16 has und 17 has Jahrhundert coming public in two books, originally in 1785 and 1788, being held in a facsimile in 1919, the latter is originating all its modern editions. The compilation of the Geheime Figuren der Rosenkreuzer is an equally proportional relevance publication of the Rosicrucian Manifestos in the 17th century; the same is arranged within a second wave of what can be understood as Rosicrucian movement or Rosicrucianism. This second stage of the Rosicrucian establishes a framework that greatly influence the lead or following names. As methodological tools, follow the propositions developed by thinkers of the Imaginarium Gilbert Durand, Jean-Jacques Wunenburger, Paul Ricoeur and Henry Corbin, using a symbolic hermeneutics and applying the phenomenology of the image, we will trace structuralism figurative present in the work focus of our study so that we envisaged and mediated by the concept of hierohistóry developed by Corbin, to understand the esotericism of the Rosicrucian movement of the 18th century in the construction and / or compilation of Geheime Figuren der Rosenkreuzer aus dem 16 has und 17 has Jahrhundert, using the symbolic emerged in the two previous century. Theosophical constituents, hermetic, alchemical and kabbalistic swarming in the work study will serve as guiding the relations established between the work and the imagery of the 18th century, that – according to the established methodology for the study of Western esotericism as bringing of Antoine Faivre and Wouter Hanegraaff – we can do the necessary similarities and differences with the Rosicrucian movement of the 17th and 18th, with a greater focus in the 18th century, which is structured the compilation of Geheime Figuren der Rosenkreuzer.